EXAMINING THE EFFECT OF THE CORONAVIRUS PANDEMIC ON EATING AND THE FOOD CONSUMPTION HABITS OF YOUNG ADULTS: THE CASE OF OSMANIYE - ULAS KADIOĞLU, Bircan (Göbeklitepe Medical Science Journal, 2024)
In this study; it was aimed to evaluate the effect of the coronavirus pandemic on eating and the food consumption habits of young adults. The study included 442 young adults aged 19-39 years. Data were obtained with a survey form questioning information on food consumption habits, before the Covid-19 pandemic and during the normalization period of the Covid-19 pandemic. Descriptive analyses were used in the evaluation of the data. The average age of the individuals participating in the study was 23.1±4.2 years and 64.7% were female. 63.6% had normal weight. The frequency of eating three meals a day was 47.1%. During the Covid-19 pandemic, 31.9% of individuals stated that the number of meals increased, 41.4% developed night eating behavior, and 38.2% gained weight. When the consumption frequency of food groups was compared with the pre-pandemic period, the consumption frequency of food groups (except for the fruit group) remained mostly unchanged. The food group with the highest increase in consumption was the fruit group (50.2%). 58.8% of young adults increased their consumption of tea, coffee and other beverages and 19.5% increased their consumption of ready-made foods. 39.4% of the participants consumed products such as medicinal plants to protect themselves from the virus. Participants' frequency of using nutritional supplements and/or herbal products increased. The most increased nutritional supplement compared to pre-pandemic period was vitamin C. The pandemic had both positive and negative effects on eating habits of young adults. As a result of the study, during the pandemic period it was evaluated that approximately one third of young adults increased the number of meals, the food consumption habits of the majority of the participants did not change, the use of dietary supplements and herbal products was found to have approximately doubled.